Public school teachers’ experiences of profound learning - Davin Jules Carr-Chellman; Michael Kroth (AS: Andragoška Spoznanja, 2019)
Teachers play a fundamental role in the democratic process by forming an educated populace. Of our many different expectations of teachers, teacher-as-lifelong-learner is among the most neglected. Our basic research questions are: what are teachers’ perceptions of profound learners and profound learning experiences. Through an in-depth focus group with public school teachers, the purpose of this study was to build our understanding of teachers-as-learners by exploring these two questions. Based on this research, the qualities of a profound learning experience include: growing, emotive, disruptive, real, irreversible, either positive or negative, social, opening, and surprising. Profound learners, according to themes which emerged: have depth of thought, are emotionally wise, take life seriously, are adventurous in thought and deed, are unbounded, and are humble. Through a constructivist lens, these qualities direct us to the following findings: profound learning is non-dualistic and holistic, is a cumulative process, and is integral to the complex role of structural identity.